1996
DOI: 10.1161/01.str.27.12.2251
|View full text |Cite
|
Sign up to set email alerts
|

Patent Foramen Ovale and Transcranial Doppler

Abstract: The injection performed before VM appeared to be the most effective TCD procedure in determining the transit of microbubbles through a PFO and subsequently in the MCAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
68
2
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 23 publications
3
68
2
1
Order By: Relevance
“…20,25 In most studies, VM was performed after injection. Zanette et al 15 were the first to systematically investigate the most appropriate timing for the performance of the VM. They also found the highest sensitivity when the VM was performed after injection compared with its performance before or during the injection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…20,25 In most studies, VM was performed after injection. Zanette et al 15 were the first to systematically investigate the most appropriate timing for the performance of the VM. They also found the highest sensitivity when the VM was performed after injection compared with its performance before or during the injection.…”
Section: Discussionmentioning
confidence: 99%
“…The injection of the contrast agent was performed before, 4,[11][12][13][14][15][16][17][18] during, 15,17,19 or after the VM. 15,20 In those studies in which the VM was performed after injection, the time delay between injection and VM was frequently not clearly specified in relation to the start or the end of injection. In the studies with a clear specification, the time from the beginning of injection to the beginning of the VM ranged between 0 and 5 seconds.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies with different CAs demonstrated that CA infusion during the VM and before the VM showed good sensitivity values compared to contrast-enhanced transesophageal echocardiography (cTEE) for RLS diagnosis, preferentially for PFO diagnosis [1][2][3][4]10 . An international consensus suggested that the VM should start five seconds after the beginning of the CA injection and should be maintained for at least five seconds 1 .…”
Section: Resultsmentioning
confidence: 99%